Patient Safety and Quality in Laboratory and Hemostasis Testing: A Renewed Loop? - Plebani, Mario; Favaloro, Emmanuel J.; Lippi, Giuseppe (Seminars in Thrombosis and Hemostasis, 2012)
More than three decades ago, George Lundberg first introduced the concept of the brain-to-brain loop for laboratory diagnostics. According to this pioneering model, the first step in the loop involves the selection of laboratory tests in the brain of the physician caring for the patient, and the final step is the transmission of test results back to the ordering physician. There are several intermediary steps, some of which are preanalytical (e.g., identification of patient and blood samples, the process of blood collection, and specimen handling); some are analytical and relate to the actual performance of the test(s); whereas others are postanalytical and involve release of test results into the medical record and further steps such as the physician's reaction to laboratory information, their interpretation of these results, and subsequent appropriate clinical action. Hemostasis testing should also be viewed within such a paradigm, so that quality throughout the total testing process can be assured. For hemostasis testing, particular attention is required to ensure provision of appropriate test samples in the preanalytical phase. Nevertheless, the timeliness of testing and an appropriate interpretation of test results are also paramount. This article overviews the concept of quality testing within hemostasis as critical to ensuring patient safety and optimal clinical and therapeutic management.
Keywords: patient safety; quality; hemostasis; testing; laboratory errors